Pendidikan Kesehatan Melalui Whatsapp Group Meningkatkan Pengetahuan dan Sikap Karang Taruna Dalam Menghadapi Bencana Tsunami Di Pesisir Pantai Tanah Lot - prasetya, kadek mahendra (PT.Mantaya Idea Batara, 2022)
WhatsApp groups on the knowledge and attitudes of youth groups in dealing with the tsunami disaster in the Tanah Lot coast. Pre-experimental research was conducted on 39 members of the youth organization in Beraban village, Kediri district, Tabanan. Before treatment knowledge, most of the community the level of knowledge and attitudes of the youth groups was measured using a knowledge and attitude questionnairein dealing with the tsunami disaster which was filled out via google form ànd distributed via whatsapp group. The result of this research indicate that most of them are male,namely51,3% and most of the respondents are 18 years old,which is 92,3%. Male respondents were 51,3% and 92,3% of respondents were 18 years old. Most (61,5%) of the respondents had a level knowledge and attitude with less qualifications in dealing with the tsunami disaster and after treatment most (59%) became good qualifications. Based in the paired t-test, it was concluded that there was significant increase (sig. =0.00) on the level of knowledge and attitudes of youth groups in dealing with the tsunami disaster on the Tanah Lot coast after being given health education through WhatsApp Group for one month.